Relationships between the expression of the ACTN3 gene and explosive power of soccer players - Domanska-Senderowska, D.; Szmigielska, P.; Snochowska, A.; Jastrzebski, Z.; Jegier, A.; Kiszalkiewicz, J.; Jastrzebska, J.; Pastuszak-Lewandoska, D.; Cieszczyk, P.; Suchanecka, A.; Wilk, M.; Brzezianski, M.; et al. (Journal of Human Kinetics, 2019)
Muscle strength and maximal speed are factors determining athlete's results during competition. Their association with ACTN3 gene activity has been documented. The purpose of this study was the analysis of ACTN3 gene expression during a 2 month training cycle of soccer players and its correlation with the countermovement jump (CMJ) and squat jump (SJ). The study group consisted of 22 soccer players (aged 17 -18). The study material included peripheral blood lymphocytes. The relative expression (RQ) of the ACTN3 gene was analyzed by qPCR and performed before and after the two -month training cycle. Before the training cycle low expression levels of ACTN3 (median RQ = 0.95) were observed, yet after the training cycle they were elevated (median RQ = 1.98) ( p = 0.003). There was an increase in performance of both jumps: SJ (p = 0.020) and CMJ (p = 0.012) at the end of the training cycle. A simultaneous increase in the ACTN3 gene expression level and height in both jump tests was observed in 73% of athletes (p > 0.05). There were no significant relationships between the ACTN3 gene expression level and the results of the CMJ and SJ. However, explosive strength is a complex feature shaped by many different factors and it could be the reason why we did not observe correlations between these variables.